Pengaruh Nilai Tukar dan Harga Kapuk Terhadap Volume Ekspor CV. Media Mitra Indonesia - Nurdiansyah, Zulfan Arya; Baroh, Istis (Universitas Galuh, 2025)
Kapok is one of the commodities derived from the randu tree. Kapok (ceiba pentandra) is a plant that grows well in both large and narrow land. Randu trees in East Java grow well and are quite large in production. One of the cities in East Java such as Pasuruan is the center of high quality kapok production. One of the companies in East Java that is engaged in the export of kapok commodities on a large scale is CV. Media Mitra Indonesia. This company has been carrying out export activities since 2014. The objectives of this study are to: (1) Analyze the causes of fluctuations in export volume, and (2) Analyze the effect of kapok price and exchange rate on export volume. The data collection technique used documentation, collecting data from existing archives. The causes of export volume fluctuations are analyzed descriptively, namely by explaining the factors that cause volume fluctuations in detail based on data that has been obtained from the company. The effect of price and exchange rate on export volume was analyzed using multiple linear regression analysis with SPSS 22. The results showed that volume fluctuations were caused by the price of kapok and the exchange rate. The price of kapok has a significant positive effect on export volume. This means that if the price of kapok is high, the company will increase the amount of production, and vice versa. Meanwhile, the exchange rate has a significantly negative effect on export volume. This means that if the exchange rate decreases, sales will also decrease, and vice versa.